METHOD OF DOCUMENT FLOW MANAGEMENT OPTIMIZATION ON THE BASIS OF MULTILAYER NEURAL NETWORKS - Ekaterina Sergeevna Savchenko (Современная наука и инновации)
The article gives an approach to the design and construction management processes optimization methods of electronic document circulation at the enterprise. The procedure for workflow modeling, adapting to the changing life cycle of the project, has been offered. The neural network has been used as an adaptive controller in simulation studies section of documents in addition to the set of mathematical tools.